The Application Of The Solfegio Method In Learning Major Instrument Practice (string) II In The Music Education Study Program, Department Of Music, Faculty Of Language And Arts, Universitas Negeri Padang - Mimanda, Fela Vio; Ardipal, Ardipal (Journal of Urban Society's Arts, 2023)
This study aims to determine whether the application of the solfegio method can improve the ability of student learning outcomes in aiming for tone in the practical learning course of major string instruments 2 of the Department of Sendratasik Music Education Study Program FBS UNP. The type of research is classroom action research (PTK) or classroom action research collaboratively using the Kemmis and Mctaggart cycle. The research subjects were students of the 2022 batch of major string instrument practice II (PIM 2) music education study program FBS UNP. The research procedure is planning, action implementation, observation, and reﬂection. Research instruments in the form of assessment test criteria sheets. Data collection techniques literature study, observation, practice assessment tests, documentation. Quantitative descriptive data analysis technique. The results showed: (1) the pre-cycle average score was 56.2 in the sufﬁcient category (C) = incomplete (2) in cycle 1 was 67 in the sufﬁcient category (B-) = incomplete, (3) in cycle 2 was 79.4 = complete. Students experienced an increase in cycle 1 of 10.8 and in cycle 2 of 12.4. The research was successful in cycle 2 meeting 2 and the results were signiﬁcant. It can be concluded that the ability of students to aim for notes in playing string instruments has increased after taking action by applying the solfegio method. So the solfegio method can be applied in learning the practice of playing string instruments.